Efficacy and safety of patient-controlled epidural analgesia versus patient-controlled intravenous analgesia following open hepatectomy: A single-center retrospective study - Xue-Peng Zhang; Wan-Ting Wei; Yong Huang; Chang-Hong Miao; Xiao-Guang Zhang; Fang Du (Heliyon, 2024)
Background: Postoperative analgesia is an essential component of enhanced recovery after surgery following abdominal surgery. Studies comparing the effectiveness of epidural analgesia with that of other analgesic modalities after liver surgery have reported inconsistent results. Consequently, the use of epidural analgesia for open hepatectomy is controversial. Objective: The present single-center retrospective study aimed to compare the efficacy and safety of patient-controlled epidural analgesia (PCEA) and patient-controlled intravenous analgesia (PCIA) in adults undergoing open hepatectomy. Methods: Patients who underwent open hepatectomy between January 2018 to December 2019 at Zhongshan Hospital, Fudan University were retrospectively analyzed. Propensity score matching was used to adjust baseline information between the PCEA and PCIA groups. The primary outcome measure was scores of the numeric rating scales (NRSs) for resting, exercise, and nocturnal pain at postoperative 24 h (postoperative day 1 [POD1]) and 48 h (POD2). The secondary outcome indicators included postoperative nausea and vomiting (PONV), hypotension, pruritus, respiratory depression, functional activity score (FAS), effective analgesic pump compression ratio, analgesic relief rate, discontinuation of the analgesic pump, reasons for discontinuation of the analgesic pump, and patient satisfaction with postoperative analgesia. Results: The NRS scores of the PCEA group on POD1 were significantly lower than those of the PCIA group (P < 0.05). On POD2, the difference between the two groups was significant only for motion NRS scores (P < 0.05). The PCIA group had significantly more patients with lower FAS functional class than the PCEA group (P < 0.001). The effective analgesic pump compression ratio and the analgesic relief rate at 2 days after the surgery were lower in the PCEA group than in the PCIA group (P < 0.001). The incidence of pump discontinuation was higher in the PCEA group than in the PCIA group on POD2 (P = 0.044). Moreover, on POD1 and POD2, the PCEA group showed a higher incidence of pruritus and hypotension than the PCIA group (P < 0.001). Both groups showed no significant difference in PONV incidence. Conclusion: In patients undergoing open hepatectomy, PCEA was more effective than PCIA in relieving moderate to severe pain on POD1. However, improving the safety and effectiveness of PCEA remains a challenge.